Electronic cigarette exposure triggers neutrophil inflammatory responses. Issue 1 (December 2016) - Higham, Andrew; Rattray, Nicholas; Dewhurst, Jennifer; Trivedi, Drupad; Fowler, Stephen; Goodacre, Royston; Singh, Dave
Abstract Background The use of electronic cigarettes (e-cigs) is increasing and there is widespread perception that e-cigs are safe. E-cigs contain harmful chemicals; more research is needed to evaluate the safety of e-cig use. Our aim was to investigate the effects of e-cigs on the inflammatory response of human neutrophils. Methods Neutrophils were exposed to e-cig vapour extract (ECVE) and the expression of CD11b and CD66b was measured by flow cytometry and MMP-9 and CXCL8 by ELISA. We also measured the activity of neutrophil elastase (NE) and MMP-9, along with the activation of inflammatory signalling pathways. Finally we analysed the biochemical composition of ECVE by ultra-high performance liquid chromatography mass spectrometry. Results ECVE caused an increase in the expression of CD11b and CD66b, and increased the release of MMP-9 and CXCL8. Furthermore, there was an increase in NE and MMP-9 activity and an increase in p38 MAPK activation. We also identified several harmful chemicals in ECVE, including known carcinogens. Conclusions ECVE causes a pro-inflammatory response from human neutrophils. This raises concerns over the safety of e-cig use.